Acute coronary syndrome leading to a new diagnosis of phaeochromocytoma following a profound intraprocedural hypertensive surge. Issue 3 (22nd March 2021) - Graby, John; Goh, Zi Wei; Haya, Naik; Carson, Kevin
Abstract : Phaeochromocytomas are rare neuroendocrine tumours, which can significantly increase the risk of cardiovascular morbidity and mortality. They are also recognised as 'the great mimic' and can present in many ways. A 42-year-old male patient presented with a non-ST elevation acute coronary syndrome and was medically treated pending an invasive coronary angiogram. During this procedure, he suffered a profound, symptomatic hypertensive surge documented with invasive pressure monitoring. This raised concern for potential secondary causes of hypertension, particularly given his age. He was subsequently diagnosed with a phaeochromocytoma, and after surgical resection of the tumour, his blood pressure control improved and he remains on single therapy only. As clinicians, it is important to remain alert for previously undiagnosed comorbidities contributing to common pathology, including rare, but life-threatening conditions as we present in this case.